2007
DOI: 10.1097/ajp.0b013e31815349bf
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Canal Size and Clinical Symptoms Among Persons Diagnosed With Lumbar Spinal Stenosis

Abstract: AP spinal canal diameter is not predictive of clinical symptoms associated with LSS. The findings also suggest that body mass may play a significant role in functional limitations observed in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 38 publications
8
71
4
4
Order By: Relevance
“…In contrast to our analysis the four studies 3,6,7,18 included in the systematic review assessed only up to three different MRI parameters with various clinical outcomes. The results of our study support the results of at least two of the earlier studies 3,6 whereas the other two studies found no strong associations.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our analysis the four studies 3,6,7,18 included in the systematic review assessed only up to three different MRI parameters with various clinical outcomes. The results of our study support the results of at least two of the earlier studies 3,6 whereas the other two studies found no strong associations.…”
Section: Main Findingsmentioning
confidence: 99%
“…Table 2 summarizes the relevant information from the studies showing no association. One study 3 used the anteroposterior spinal canal diameter and the other study 6 a grading of canal stenosis (ratio:…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was reported that WC was correlated to vibration sense 19,20) , intensity of pain 19) , balance ability 20) , and body weight 21,22) . In this study, actual WC was correlated with muscle strength in ASLR independent of age or body weight.…”
Section: Discussionmentioning
confidence: 96%
“…However the narrow lumbar canal would result from the fact that the size of the dural sac is inadequate to that of the lumbar canal. According to the studies of Geisser et al [15], in normal conditions, there is an empty space between the lumbar canal and its content, enabling free movement of the content, without tension or pressure during movement of the lumbar spine. An abnormal reduction of this empty space between the lumbar canal and its content would be the cause of the nervous suffering.…”
Section: Lumbar Canal (Apd1) Dural Sac (Apd2)mentioning
confidence: 99%